KOMPARASI PENDAPATAN PETANI KOPI ORGANIK DAN KONVENSIONAL (Suatu Kasus di Desa Margamulya, Kecamatan Pangalengan, Kabupaten Bandung, Jawa Barat) - Rahma Az-Zahra Saroja; Tuti Karyani (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
The demand for organic products is increasing because of changes in consumer patterns or lifestyles. Awareness of the dangers used synthetic chemicals in agricultural cultivation makes organic farming or sustainable agriculture attract the attention of consumers and producers of organic coffee. The government supports the trend of organic products by forming a program of 1,000 organic farming villages. This study aims to analyze differences in income of organic and conventional coffee farmers. This research was conducted in Margamulya Village, Pangalengan Regency, West Java. Margamulya Village as the center of West Java coffee production and one of the villages chosen as one of the organic villages in the 1000 organic farming village program in Indonesia. The sample used in this study was 56 respondents consisting of 28 organic farmers and 28 conventional farmers obtained through the Slovin formula and taken by area sampling methods. The method used in this research is comparative quantitative research methods. Data analyzed with comparative income analysis using the Independent Sample T-Test. The analysis shows that the income of conventional farmers is higher than organic farmers. The production of organic coffee farmers still lower then conventional farmers because they are still new to applying the organic cultivation system. Organic farmers have not received a premium price for their organic coffee products.